SOCIO-PSYCHOLOGICAL ASPECTS OF PROFESSIONAL COMMUNITY DEVELOPMENT (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The author investigates origins and the essence of the term "community", analyzing sociological and socio-psychological community theories. The researches that she did were distinct different types of the community and analyze its structural components. In the article are also provided results of a qualitative research of the psychological aspects of mental health and counseling professional community.
Keywords: professional community, local community, community orientation